A cat's scratch or a wolf's bite?. (October 2020) - Shmuely, Haim; Chernin, Gil; Giladi, Michael; Zimhony, Oren; Miller, Edward Bari
Bartonella henselae endocarditis mimicking systemic vasculitis has been reported in patients with valvulopathy. Herein, we describe a patient with B. henselae endocarditis involving a prosthetic pulmonic valve with positive anti-dsDNA antibodies misdiagnosed with systemic lupus erythematosus (SLE) based on the revised classification SLE criteria.